Analisis Keterampilan Berpikir Kreatif Siswa SMA Negeri 4 Gorontalo Dalam Menyelesaikan Soal Hots Pada Materi Laju Reaksi - Mangara Sihaloho; Asaria Dakhi; La Alio (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to determine the achievement of aspects of students' creative thinking skills and the data collection technique for this research uses an essay test with 4 questions, this research is qualitative research, the sample in this research is 100 students of class XI-IPA. The results of the research show that students' creative thinking skills as a whole fall into the quite creative category with an average total percentage of 60%. With the level of students' creative thinking skills in solving High Order Thinking Skills (HOTS) questions on the reaction rate material in the fluency aspect of 58% in the quite creative category, in the flexibility aspect it was 53% in the quite creative category, in the originality aspect it was 70% in the quite good category, and the level of students' creative thinking skills in the elaboration aspect was 59% in the quite creative category.